Effect of Reservoir Heterogeneity on Gas Assisted Gravity Drainage Project - Tham , Boon Keat (2010)
The main energy to move reserve oil to the production well is the pressure difference between reservoir and bottom hole. To maintain the pressure difference, operators need to introduce some form of artificial drive. The major problem in applying WAG (Water Alternate Gas) is gravity segregation effects. The injected gas tend to override while the water underride. GAGD (Gas Assisted Gravity Drainage) process was suggested as an alternative method which utilized advantage of the natural segregation. The objectives of the research are to visualize the development of the downward movement towards the horizontal producer, investigate the effect of different kv/kh(overall vertical permeability/overall horizontal permeability),layers arrangement, and different k (permeability) values with same kv/kh on FOE (recovery factor). Investigations have been done by using Schlumberger ECLIPSE 100. Results show that for heterogeneous model, lower kv/kh will yield a higher FOE. For the same kv/kh, model with a decreasing-downward k will yield a higher FOE. Lastly, models with same kvn/kv (permeability at nth layer/overall vertical permeability) show a same displacement phenomenon. Thus yield a similar FOE.